Pharmacological evaluation of the hydro-alcoholic extract of Campomanesia phaea fruits in rats - Wczassek,L. R. (2020)
Abstract Campomanesia phaea (Myrtaceae), popularly known as cambuci, is one of several species of plants producing comestible fruits, largely used in human nutrition. Despite its consumption and economic potential, limited scientific research is available on the Campomanesia, especially those related to its therapeutic benefits. It is reported by traditional medicine the use of the plant in the treatment of different disorders, such as cardiovascular and nervous system disturbances. So, the aim of this study was to carry out the pharmacological evaluation of the hydro-alcoholic extract (HAE) of Campomanesia fruits in rats by screening consisting of tests: a) neuropharmacological observation, b) test on the cardiovascular system. The HAE, prepared from the extraction of fruits with water/ethanol, was concentrated and freeze-dried. Behavioral responses in rats were investigated in open field test and the cardiovascular actions were investigated by a register of indirect blood pressure and the register of spontaneous beating rate right atrium. The results revealed that HAE induced grooming, hypotension and bradycardia. So, this study identified an action on the central nervous system, represented by grooming, and a cardiovascular activity of Campomanesia. The hypotension, attributed in part to bradycardia, was not related to a cholinergic effect, discarding a possible cholinomimetic action of the plant that could justify both cardiovascular and central actions.